Analytical stabilization of modulated optical similaritons in a tapered graded-index waveguide. (January 2016) - Goyal, Amit; Gupta, Rama; Raju, Thokala Soloman; Kumar, C N
Abstract: We note that the self-similar waves recently reported, in a tapered graded-index waveguide, severely suffer from extreme increase in the amplitude, after traversing a finite distance. In this work, we theoretically described that by adding a suitable homogeneous background in the expression for widths of the self-similar solutions which is achievable through the modulation of tapering profile, we could avert this situation. We further find that the self-similar waves propagate in the nonlinear waveguide, quite a distance stably, albeit they undergo self-compression.